Incidencia de la cultura financiera en la gestión económica y financiera de agroindustria Molino Don Sergio E.I.R.L. distrito de San Jose año 2015 - Rodriguez Mendoza, Delia Marita (2016)
The present investigation there treats on the financial culture and his incident in the economic and financial management of Agroindustry Mill Don Sergio E.I.R.L - District of San Jose year 2015. And there has as general aim determine the incident of the financial culture in the economic and financial management of Agroindustry Mill Don Sergio E.I.R.L - District of San Jose year 2015. For the development of the above mentioned aim, technologies of investigation were in use as the interview to the Manager of the Company Agroindustry Mill Don Sergio E.I.R.L of the District of San Jose, Where one tries to announce the topic, likewise to detect the areas in which it is necessary to to have more interest great and to be able to implement schemes that help to a better procedure of all his activities, also the application of financial indexes what will allow to detect in time the critical points of the company, to take the most correct decisions at the right moment, To the realized investigation it is possible to say since conclusion that the incident of the financial culture in the economic and financial management of Agroindustry Mill Don Sergio E.I.R.L - District of San Jose year 2015 is favorable because it will allow to define the areas that need major interest achieving this way the optimization of resources, a better capture of decisions and a good economic and financial management on the part of the different representatives of the companies beside knowing early the economic and financial results of the above mentioned companies that apply it.